Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1093/nar/gkl646
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dicer and Argonaute down-regulation on mRNA levels in human HEK293 cells

Abstract: RNA interference and the microRNA (miRNA) pathway can induce sequence-specific mRNA degradation and/or translational repression. The human genome encodes hundreds of miRNAs that can post-transcriptionally repress thousands of genes. Using reporter constructs, we observed that degradation of mRNAs bearing sites imperfectly complementary to the endogenous let-7 miRNA is considerably stronger in human HEK293 than HeLa cells. The degradation did not result from the Ago2-mediated endonucleolytic cleavage but it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 51 publications
10
172
2
Order By: Relevance
“…However, an increasing body of evidence suggests that miRNA-mRNA interaction leads to a de-stabilization of mRNA leading to alteration in mRNA levels, albeit modest. Although enough evidence of alteration of transcript levels exists in microarray experiments, 18 the exact mechanism has only been partially elucidated in Drosophila melanogaster and zebrafish. 19,20 Experiments have shown that the P body protein GW 182 marks the mRNA for decay.…”
Section: Micrornas Regulate Gene Expressionmentioning
confidence: 99%
“…However, an increasing body of evidence suggests that miRNA-mRNA interaction leads to a de-stabilization of mRNA leading to alteration in mRNA levels, albeit modest. Although enough evidence of alteration of transcript levels exists in microarray experiments, 18 the exact mechanism has only been partially elucidated in Drosophila melanogaster and zebrafish. 19,20 Experiments have shown that the P body protein GW 182 marks the mRNA for decay.…”
Section: Micrornas Regulate Gene Expressionmentioning
confidence: 99%
“…42 Reporters measuring activity of endogenous Let-7 and miR-30 showed that ability of miRNAs to repress translation is strongly reduced during oocyte growth and maturation while RNAi-like cleavage was less affected. Interestingly, the less abundant miR-30 apparently retained more silencing activity suggesting that additional mechanism(s) reduce Let-7 activity in the oocyte.…”
Section: Mammalian Mirna and Rnai Pathwaysmentioning
confidence: 99%
“…The miR-9500 is transcribed from an intergenic region and yields a 19 ntmature sequence. The gene encoding miR-9500 is located on chromosome 3, and the mature sequence is generated through dicer-dependent processing 31 ( Supplementary Figure 4). In addition, we found that miR-9500 was expressed in almost all cells (Supplementary Figure 5), and the mature sequence of miR-9500 is conserved in other mammals (Figure 1b).…”
Section: Discussionmentioning
confidence: 99%